Correlation of lipoprotein (a) concentration with the extent of coronary artery disease in patients on lipid lowering therapy - Malek, Filip; Dvorak, Jan; Svitil, Jan; Skalnikova, Vladimira; Mates, Martin; Kmonicek, Petr; Formanek, Pavel; Aschermann, Ondrej; Kopriva, Karel; Neuzil, Petr (Neuro endocrinology letters, 2012)
OBJECTIVES: Lipoprotein (a) [Lp(a)], together with other serum lipoproteins have an important role in the pathogenesis of coronary heart disease. The objective of the study was to assess the association between plasma levels of Lp(a) with the extent of angiographically defined coronary artery disease (CAD). PATIENTS AND METHODS: A total of 518 consecutive patients (66 % males) underwent coronary angiography in connection with lipids and lipoprotein determinations between 1st January and 31st May 2010. Most of the patients were treated with lipid lowering therapy (77 % statins). Modified angiographic Gensini Score (GS) and adjusted angiographic score (AS) were used to reflect the extent of coronary atherosclerosis. RESULTS: Both GS and AS angiographic scores correlated significantly with age, male gender, statin therapy and inversely with left ventricular ejection fraction (p<0.05-0.01 for all). The results showed significant inverse correlation of HDL cholesterol levels with GS and AS (r=-0.16, p<0.001), and apolipoprotein A levels with GS and AS (r=-0.20, p<0.0001) and a positive correlation of Lp(a) levels with angiographic score (r=0.13, p<0.01) and with adjusted angiographic score (r=0.16, p<0.01). Regression analysis showed only Lp(a) concentration was an independent lipid factor that correlated with the extent of CAD. CONCLUSION: Only Lp(a) levels correlated with the extent of coronary artery disease as assessed with coronary angiography in patients treated with lipid lowering therapy.
Keywords: Female; Hypolipidemic Agents; lidé středního věku; Severity of Illness Index; Logistic Models; kohortové studie; mužské pohlaví; rizikové faktory; Coronary Artery Disease; dyslipidemie; Dyslipidemias; senioři nad 80 let; Humans; dospělí; logistické modely; hypolipidemika; stupeň závažnosti nemoci; lipoprotein (a); Lipoprotein(a); lidé; Middle Aged; Cohort Studies; Aged, 80 and over; senioři; ženské pohlaví; Risk Factors; nemoci koronárních tepen; Aged; Adult; Male